EACVI survey on hypertrophic cardiomyopathy - Podlesnikar, Tomaz (2022)
Publisher Copyright: Published on behalf of the European Society of Cardiology. All rights reserved. © The Author(s) 2021. For permissions, please email: journals.permissions@oup.com.